2010
DOI: 10.1007/s12257-009-0142-8
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, antibacterial, tyrosinase inhibitory, and biofilm inhibitory activities of fermented rice bran broth with effective microorganisms

Abstract: The effective microorganism fermentation extract (EM-X) is a refreshment beverage widely consumed in East Asia. Due to the antioxidant property of the health beverage, EM-X has potential benefits for the human immune system and has been generally accepted in clinical practice. In search of new functions of EM-X, another version of EM-X, named EM-YU in this study, which is fermented from rice bran, seaweed, and kiwifruit with effective microorganisms demonstrates high antioxidant, antibacterial, tyrosinase inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
(44 reference statements)
1
9
0
Order By: Relevance
“…These drinks exhibited the ability to inhibit inflammation, to prevent asthma, osteoporosis, Parkinson's disease and cancer cell growth without showing any toxicity as demonstrated in appropriate animal models . These drinks also displayed antibacterial activity including reduction of the biofilm formation . Our results indicate that, additionlly, apples and their leftovers may serve as raw material for production of similar health promoting foods.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…These drinks exhibited the ability to inhibit inflammation, to prevent asthma, osteoporosis, Parkinson's disease and cancer cell growth without showing any toxicity as demonstrated in appropriate animal models . These drinks also displayed antibacterial activity including reduction of the biofilm formation . Our results indicate that, additionlly, apples and their leftovers may serve as raw material for production of similar health promoting foods.…”
Section: Discussionmentioning
confidence: 62%
“…52 These drinks also displayed antibacterial activity including reduction of the biofilm formation. 53 Our results indicate that, additionlly, apples and their leftovers may serve as raw material for production of similar health promoting foods.…”
Section: Discussionmentioning
confidence: 70%
“…As summarized in Table 3, B. cepacia TKU025 resulted in the lowest IC 50 value in the tyrosinase inhibitory activity with the cheapest culture medium compared with the other reports of tyrosinase inhibitor-producing strains [3,17,21]. In addition, the tyrosinase inhibitor of B. cepacia TKU025 also showed antibacterial activity against E. coli and B. cereus TKU006, and antifungal activity against A. fumigatus and F. oxysporum.…”
Section: Discussionmentioning
confidence: 88%
“…Similar to most of the other tyrosinase inhibitors [10,[22][23][24], TKU025 tyrosinase inhibitor was also suspected to be phenol-containing compounds according to the results of a partial purification by liquid-liquid partition approach within a twophase solvent system and column chromatography. Many reports indicated a Table 3 Comparison of C/N source of tyrosinase inhibitor production and the 50 % inhibition concentration (IC 50 ) for tyrosinase inhibitory activity by different microorganisms A. oryzae BCRC 32288 Soygerm 0.19 [3] Microorganisms (more than 100 bacterial strains) Rice bran 1.49 [21] Squid pen fermented with Burkholderia cepacia TKU025 6115 significant correlation between total phenolic content and antioxidant activity [25]. Besides, it was confirmed that phenolic compounds showed tyrosinase inhibitory activity [26].…”
Section: Discussionmentioning
confidence: 99%
“…Although many synthetic antioxidants are promising for various human ailments, their pro-oxidant or cytotoxic nature at higher concentrations prevents their long-term use. These findings, together with consumer interest in natural foods, have increased the attention devoted to the development of alternative antioxidants from natural products [4].…”
Section: Introductionmentioning
confidence: 99%